Nucleotide sequence of a segment of Drosophila mitochondrial DNA that contains the genes for cytochrome c oxidase subunits II and III and ATPase subunit 6. - Clary, D O (1983)
The nucleotide sequence of a segment of the mtDNA molecule of Drosophila yakuba has been determined, within which have been identified the genes for tRNAleuUUR, cytochrome c oxidase subunit II (COII), tRNAlys, tRNAasp, URFA6L, ATPase subunit 6 (ATPase6), cytochrome c oxidase subunit III (COIII) and tRNAgly. The genes are arranged in the order given and all are transcribed from the same strand of the molecule in a direction opposite to that in which replication proceeds around the molecule. The tRNAlys gene is unusual among mitochondrial tRNAlys genes in that it contains a CTT anticodon. The triplet AGA is used to specify an amino acid in all of the COII, COIII, ATPase6, and URFA6L genes. However, the AGA codons found in these four polypeptide genes correspond in position to codons which specify nine different amino acids, but never arginine, in the equivalent polypeptide gene which have been sequenced from mtDNAs of mouse, yeast and Zea mays.